Spread of vimentin‐immunoreactive cells within the plaque‐like lesion in the spinal anterior horn of a patient with post‐poliomyelitis syndrome. Issue 5 (19th September 2021) - Hineno, Akiyo; Oyanagi, Kiyomitsu; Yoshida, Takuhiro; Sakai, Yasuhiro; Kanno, Hiroyuki; Sekijima, Yoshiki
Abstract : A Japanese man in the present study experienced acute weakness in his right leg as a two year old. The strength in his leg gradually recovered and developed, and he could play golf and climb mountains up to around the age of 50. From approximately 55 years of age, he became unable to stand up from a stooped position. Muscle weakness and atrophy spread to his right arm, and an electromyography revealed a neurogenic pattern in his lower and upper extremities. The patient was diagnosed as having post‐poliomyelitis syndrome (PPS). Numbness in both the legs and pain in the buttocks occurred after 60 years of age. Computed tomography and magnetic resonance imaging at that time revealed spondylosis and protrusion of an osteophye in lower thoracic vertebrae compressing the second lumbar segment of the spinal cord. He died of malignant lymphoma and acute interstitial pneumonia at 80 years of age. Pathological examination revealed transverse myelopathy at the second lumbar segment of the spinal cord and total necrosis. The anterior horn and the intermediate zone of the third and fourth lumbar segments of the spinal cord on the right side were atrophic and diffusely gliotic. An oval‐shaped plaque‐like lesion was observed in the right anterior horn at the third and fourth lumbar segments of the spinal cord. Neurons and synaptophysin immunoreactivity had completely disappeared in the plaque‐like lesion. A striking spread of vimentin‐immunoreactive cells was found corresponding to the lesion, while glial fibrillary acidic protein‐immunoreactive astrocytes existed evenly in the anterior horn and intermediate zone on both sides of the third and fourth lumber segments of the spinal cord. Virological examination using the autopsied materials was negative for poliovirus. Neither transactivation response DNA‐binding protein of 43 kDa‐immunoreactive inclusion nor Bunina body was seen in the spinal cord. The present paper demonstrates new findings of a noteworthy response of the vimentin‐immunoreactive cells within the peculiar "plaque‐like lesion" in the PPS.